Determination of D- and L-amino acids produced by cyanobacteria using gas chromatography on Chirasil-Val after derivatization with pentafluoropropyl chloroformate - Zahradnícková, Helena; Husek, Petr; Simek, Petr; Hartvich, Petr; Marsálek, Blahoslav; Holoubek, Ivan (Analytical and bioanalytical chemistry, 2007)
A rapid and simple method was developed for the determination of free amino acids (AAs) released from cyanobacteria. The procedure involves trapping of AAs from the centrifuged cyanobacterial culture fluid on a cation-exchange resin, their release together with the resin by direct treatment with the reaction medium, followed by immediate derivatization with a corresponding chloroformate. The extractive alkylation transfers the analytes into an organic phase, an aliquot of which is subjected to GC analysis. Identification and quantification of AAs was performed by GC/MS and GC/FID, respectively, using propyl chloroformate (PCF) as the derivatization reagent. For chiral analysis, the cyanobacteria extracts were treated with 2,2,3,3,3-pentafluoropropyl chloroformate (PFPCF) to create more volatile analytes. Separation of the AA enantiomers was accomplished on a Chirasil-Val capillary column and the D/L enantiomeric ratios were determined. AAs of cyanobacteria are considered to be important for the assessment of energy flow in an aquatic food web, nutrition value of cyanobacteria in a food web and for cell-cell communication within cyanobacteria. The highest levels of AAs were found in the summer period at the beginning of the season (July). In the September and October samples, the amount of AAs was lower, the number of D-AAs decreased and the D/L ratio was higher than in the July sample. Based on the obtained results it can be assumed that young populations excrete AAs in higher concentrations and a different composition compared to actively growing populations.
Keywords: Chromatography, Gas; chromatografie plynová; Seasons; Cyanobacteria; Amino Acids; Formates; sinice; roční období; formiáty; aminokyseliny